Teorema de Riemann-Roch, morfismos de Frobenius e a hipótese de Riemann - Silva Junior, Roberto Carlos Alvarenga da [UNESP] (2014)
The aim of this work is to estimate a bound for the number of rational points of a curve. Observing the various similarities between the ring of integers and the ring of polynomials in one variable, we use tools from number theory to solve a problem of algebraic geometry. From this merger is born one of the noblest areas of mathematics: arithmetic geometry. Making use of the famous Riemann-Roch's theorem and tools of number theory we demonstrate the Riemann hypothesis for the zeta-function of a nonsingular curve and which consequence this hypothesis has to count rational points on a curve